The ways to meet the Church’s needs resulting from the worship of god - Mazur, Karolina (Prawo Kanoniczne, 2021)
Meeting the needs of the Church is one of the most important responsibilities of the members of the People of God. Clergy and laity fulfill the duty of can. 222 § 1 KPK, providing financial support, also spiritual and personal assistance. The financial benefits of the faithful include tax liabilities, acts of life (donation) or death (testamentary ordinances), voluntary victims of the faithful and fees for the exercise of acts of executive power or for the execution of the Holy See’s records. The faithful provide the Church with economic support by organizing and supporting collections. Church legal persons may benefit from tax exemptions after fulfilling the conditions provided for in the secular law and ask the faithful for subventions. The Church’s needs, arising from the worship of God, may require personal benefits. All the faithful can give their lives to God and start working for the good of the Church, ordaining priests, living in celibacy or marriage. Clergymen and members of institutes of consecrated life and associations of apostolic life realize can. 222 § 1 KPK through pastoral ministry. The faithful can take part in cleaning, decorating or renovation works in holy places, take part in collections as a volunteer to obtain funds for the maintenance of sacral buildings. They can also take legal actions aimed at introducing changes in state law, so that all the faithful can participate in the Eucharistic Sacrifice on Sunday and church holidays. All the faithful, according to their own position, should strive to lead a holy life. The clergymen should enable the faithful to use the sacraments, participate in the liturgy of the hours (can. 1174 § 2 KPK), prepare for the profession, the consecration rite, the dedication of the church or the altar, blessing of things or persons.